(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Objectives: To assess the pregnancy outcome and health status of the offspring of women conceived within 2 years of RAI therapy. Study design: A case control study of 27 pregnant women, where evaluation of pregnancies and health status of offspring in further follow-up were done of 17 cases who got pregnant within 2 years of receiving radioiodine therapy for differentiated thyroid cancer, and the control group consisted of 10 healthy pregnant women of the same age group without any thyroid disorder. Results: Among 17 cases, 8 (47.0%) were conceived within one year of the administration of I-131. One (5.9%) of 17 patients had hypertensive crisis (pre-eclampsia), and two (11.7%) showed preterm labor, which was not significant and not dependent on the therapeutic dose of 131-I or time interval. The mean birth weight (2972.4 ± 376.7 gm) and birth length (46.1±2.6 cm) of children in the study cases were significantly lower compared to children in the control group (3230 ± 179.5 gm; 49.2 ± 1.1 cm). No congenital anomaly, abnormal thyroid hormone level, or sonographically detectable thyroid gland abnormality were found. The normal neuropsychomotor development of their children and good school performances were assured. There was no case of miscarriage, stillbirth, or neonatal death. All the children are healthy now. Conclusion: Although the study showed that radioiodine therapy has no significant effect on pregnancy outcomes or the health status of offspring, precautions should be taken to avoid risky pregnancies, and patients should be encouraged to conceive after an adequate time interval after therapy. Bangladesh J. Nuclear Med. 26(2): 140-145, 2023